An invitation to environmental sociology - Bell, Michael, 1957- (Thousand Oaks, Calif. : Pine Forge Press, 2012)
'The highly praised Fourth Edition of An Invitation to Environmental Sociology brings out the sociology of environmental possibility, inviting students to delve into this rapidly changing field. Written in a lively, engaging style, Michael Bell covers the broad range of topics in environmental sociology with a personal passion rarely seen in sociology textbooks. With extensively updated material on the environmental situation, this edition challenges readers with the complexity of environmental puzzles'--Provided by publisher.
Machine generated contents note: Chapter 1. Environmental Problems and Society Part I: The Material Chapter 2. Consumption and Materialism Chapter 3. Money and Machines Chapter 4. Population and Development Chapter 5. Body and Health Part II: The Ideal Chapter 6. The Ideology of Environmental Domination Chapter 7. The Ideology of Environmental Concern Chapter 8. The Human Nature of Nature Chapter 9. The Rationality of Risk Part III: The Practical Chapter 10. Mobilizing the Ecological Society Chapter 11. Governing the Ecological Society .
Includes bibliographical references and index.
Keywords: Environmental sociology; Environmental responsibility; Environmental ethics